Empirical Investigation of Islamic Banking Adoption in Brunei - Ali, Qaisar; Yaacob, Hakimah Binti; Haji Mahal, Dayang Hjh Norliza Binti Dato (International Journal of Islamic Banking and Finance Research, 2018)
The main objective of this study is to explore the understanding level of various Islamic banking concepts and determine the factors that impact the adoption of Islamic banking services in Brunei. The impact of thelevel of understanding, relative advantage, compatibility, complexity, observability, uncertainty, and service quality was examined through Rogers (2003) Diffusion of Innovation. The study adopted quantitative approach; data were collected through a self-administrated questionnaire from 245 bank customers located in Brunei’s Muara district.The findings predicted that understanding level of various Islamic banking concepts was below average among Islamic bank customers. The multiple regression analysis predicted that understanding, relative advantage,compatibility, complexity, observability, uncertainty and service quality has apositive impact on theadoption of Islamic banking services.